O lugar de expressão dos jovens comunicadores: discursos sobre concessão e conquista - Medeiros, Frederico Pinheiro de Souza (2021)
In recent decades, technological changes have become more visible, with implications for the way people relate and communicate. Understanding this phenomenon is, therefore, an important factor for a better comprehension of society. In the world, many young people live actively in the digital environment. It is noteworthy that access conditions are not the same for all young people, and it is often up to public policies to transform this reality. This research aims to identify how young communicators who are members of CUCA Mondubim's Communication Monitoring Program understand, constitute and reveal themselves as communicators in the institutional space of CUCA and in its social networks. For this, there was a face-to-face observation of the monitors in their daily activities. It started with a reflection on the implications of advances in Information and Communication Technologies (ICTs), having as references, academics such as Comparato (2001) and Peruzzo (2007), which created an interlocution with the views on Public Policies and Public Policies for Youth of authors such as Ramos (2005) and Oliveira and Barbalho (2018). The research assumes an ethnographic inspiration regarding the data collection and analysis process. The ideas that guide the methodological procedures are supported by Geertz (1989), Magnani (2002) and Malinowski (2018). It became essential to go to the field, between the months of October and December 2019, to observe the training of monitors, agenda meetings, recordings and productions. In 2021, in order to qualify the analyses, semi-structured interviews were carried out (DUARTE, 2004; BONI, QUARESMA, 2005) and we evaluated, through Discourse Analysis (FOUCAULT, 1996; CAREGNATO, MUTTI, 2006), content produced by the monitors. It is concluded, from the data analysis, that there is a focus of the PPJ on employability and, therefore, a more technical than theoretical/critical training. As the structure is previously established by the managers, young communicators have little control over the content produced by Monitoring. Young people understood themselves as communicators based on their work, when they put their communicational knowledge into practice. Thus, for young people, being a communicator is directly linked to the craft, practice and execution of tasks, respecting an institutional framework and technical quality control. KEYWORDS: Communicator. Youth. Public policy. CUCA.